The Role of Speech Communication in the Development of Learning Objectives in the General Education Program at James Madison University - Fuller, Rex M. ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
As early as 1993 James Madison University realized that a significant revision was necessary in its undergraduate core curriculum. A General Education Committee was formed which undertook a review and evaluation of 1352 objectives; the Committee produced and published a list of approximately 100 specific learning objectives. These learning objectives were then refined into clusters: Cluster 1, Skills for the 21st Century; Cluster 2, Arts and Humanities; Cluster 3, The Natural World; Cluster 4, Social and Cultural Processes; and Cluster 5, Individuals in the Human Community. The university then undertook the establishment of the office which would manage and supervise the design, development, delivery, and evaluation of the General Education program. All matriculated students are required to complete Cluster 1 during their freshman year. The faculty has created "Cluster 1 packages"--a package is a nine hour curriculum of course work, drawn from a variety of academic departments. Speech communication is the only discipline represented in every package and has evolved into the central player in Cluster 1. The 1997-98 academic year was the first year of the General Education program and the first full year of Cluster 1 implementation. Over 3000 freshmen were accommodated during the first two semesters, and the program's success is being measured by an intensive assessment program. The principal challenges facing Cluster 1 in general and speech communication in particular are continuing to refine the focus of cluster learning objective statements, the creation of appropriate assessment instruments, and the implementation of learning activities in cluster packages. (Contains 6 references. Appended is the Cluster 1 learning objectives list.) (NKA)
ERIC Note: Paper presented at the Annual Meeting of the National Communication Association (84th, New York, NY, November 19-24, 1998).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cognitive Objectives; College Freshmen; Core Curriculum; Curriculum Development; General Education; Higher Education; Program Descriptions; Speech Communication; Cluster Courses -- James Madison University VA; Curriculum Implementation -- Curriculum Review Development and Implementation; Reports, Descriptive; Speeches/Meeting Papers